2002
DOI: 10.1002/art.10313
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of intraarticular corticosteroid therapy for coxitis in juvenile rheumatoid arthritis

Abstract: Objective. To study the efficacy and safety of intraarticular triamcinolone hexacetonide (IATH) for the treatment of coxitis in patients with juvenile rheumatoid arthritis (JRA).Methods. Fifty consecutive patients with JRA and coxitis were studied prospectively. Forty-eight children received IATH in 67 arthritic hips. The remaining 2 children exhibited 3 cases of femoral head necrosis (FHN) at the initial assessment and were only followed up; both were receiving long-term systemic steroids. After a minimum of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(27 citation statements)
references
References 26 publications
1
22
0
4
Order By: Relevance
“…The potential role of GC injection in the hip in causing avascular necrosis of the femoral head is unclear. Reported studies suggest that the risk is small and is probably increased by the simultaneous administration of systemic GCs [21,22]. …”
Section: Intra-articular Gcsmentioning
confidence: 99%
“…The potential role of GC injection in the hip in causing avascular necrosis of the femoral head is unclear. Reported studies suggest that the risk is small and is probably increased by the simultaneous administration of systemic GCs [21,22]. …”
Section: Intra-articular Gcsmentioning
confidence: 99%
“…Important side effects of corticosteroids are listed in Table 3. Corticosteroids can be administered systemically (orally or parenterally) or locally [3].…”
Section: Corticosteroidsmentioning
confidence: 99%
“…If hygienic standards are followed, the risk of infection is low [5]. Aseptic bone necrosis, especially of the femoral head, is associated with systemic corticosteroids but not with intra-articular corticosteroids injected into the hip [3].…”
Section: Intra-articular Injections With Corticosteroidsmentioning
confidence: 99%
“…(23) Another study reported three incidents of femoral head necrosis out of 67 IAG injections. However, these cases were found exclusively in the context of concurrent systemic corticosteroids, (24) thereby making it difficult to strictly determine IAG as the cause of femoral head AVN.…”
Section: Introductionmentioning
confidence: 99%